Reducing Manufacturing Lead Time With Lean Manufacturing Approach Case Study: CV Suho Garmindo - Yusup Mauluddin; Sopia Marwah (UNIVERSITAS PAKUAN, 2023)
The purpose of this study is to reduce the Lead Time Manufacturing of mask products at CV Suho Garmindo. At this time it is known that Lead Time Manufacturing is influenced by Non-Value-Added activities and Necessary Non-Value Added activities in which there are several wastes that occur, these activities include the temporary storage process in the loading section, the process of reworking defective products and the transportation process. The method used is Lean Manufacturing, the tools used are Value Stream Mapping (VSM) and Process Cycle Activity (PAM). Value Stream Mapping is used to identify activities that have a cycle time greater than the takt time, followed by Process Cycle Activity mapping to analyze activities that are Non-Value Added activities. Furthermore, NVA activities are analyzed with 5W1H, and 5 why's tool to find out the root of the problem. Based on the research results from 126.1 minutes of lead time process 110 minutes is a non-value added activity. The rework process is identified as having the largest value of contributing lead time, so rework must be eliminated. After it is known that the root cause of the rework process is due to the ineffectiveness of the sewing process (bottleneck occurs), then for improvement the author proposes the needs of the available machines and man power. The changes are the number of machines from 9 to 10, sonday operators from 2 people to 1 person, finished stick operators from 2 people to 1 person, and funnel operators from 2 people to 4 people. Furthermore, the optimal layout improvement based on production flow is described. Due to research limitations, this research did not reach the implementation stage. So with the change in the number of machine requirements and available man power, it is expected that the rework process will be reduced so that the Manufacturing Lead Time can be reduced.